2023
DOI: 10.1002/anie.202308838
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Multidimensional Kinetic Screening in Continuous Flow Reactors

Bo Zhang,
Ansila Mathoor,
Tanja Junkers

Abstract: An automated high throughput multidimensional reaction screening platform based on an inline Fourier‐transform infrared spectroscopy (FT‐IR) is presented. By combining flow chemistry, machine automation and inline analysis, the platform is able to screen reactions in multidimensions (residence time, monomer concentration, degree of polymerization, reaction temperature and monomer conversion) rapidly and efficiently way. Kinetic data libraries associated with high data precision (absolute error < 4 %), high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…12–15 Dynamic experiments have been developed and demonstrated by various groups, but, thus far, used exclusively for homogeneous reactions. 16–24 Application of this technique to heterogeneously-catalyzed gas–liquid reactions, however, has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…12–15 Dynamic experiments have been developed and demonstrated by various groups, but, thus far, used exclusively for homogeneous reactions. 16–24 Application of this technique to heterogeneously-catalyzed gas–liquid reactions, however, has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] Recent developments in microchemistry have led to the investigation of polymerization through flow synthesis, initially facilitated by micromixer-based systems. [42][43][44][45][46][47] Flow synthesis offers several benefits, including homogeneous mixing, efficient heat exchange, precise residence time control and scalability [48][49][50] , making it a suitable candidate for integration with machine learning techniques. [51][52][53][54][55][56][57] Warren et al previously developed a polymer synthesis and analysis platform that allowed RAFT polymerization to be automated and used this system to explore the trade-off between molar mass dispersity and monomer conversion 58 .…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic modeling, grounded in a comprehensive understanding of chemical processes, represents a classical and crucial strategy for reaction optimization, especially for heterogeneous hydrogenation reactions. [14][15][16][17] For instance, Su et al demonstrated the application of kinetic modeling in the heterogeneous flow hydrogenation of hexafluoroacetone trihydrate, revealing an adsorption-desorption mechanism with competitive adsorption of H2 dissociation. [18] Similarly, Yu et al conducted a continuous hydrogenation study of 2-(4-nitrophenyl) butanoic acid and kinetics study in a micropacked-bed reactor, employing kinetic analysis to elucidate the impacts of internal and external diffusion, as well as salt formation.…”
Section: Introductionmentioning
confidence: 99%